Improving tax compliance establishing a risk management framework. (Asian Development Bank, 2017)
Compliance risk management is a systematic approach to manage taxpayer compliance as well as support organizational structures and strengthen their enabling capabilities. Intended for use by revenue bodies seeking to implement or strengthen their current frameworks, the brief was sponsored by the Asian Development Bank Domestic Revenue Mobilization Trust Fund with a contribution from the Government of Japan.